CCD Photometry of the Globular Cluster NGC 4372 - Hong-Suh Yim; Young-Wook Lee; Mun-Suk Chun (Journal of Astronomy and Space Sciences, 1994)
We present a deep (B, V) color-magnitude diagram (CMD) of the Galactic globular cluster NGC 4372. According to the recent inside-out picture of Galaxy formation, this cluster is predicted to be one of the oldest globular clusters in the Galaxy. Our CMD shows a well defined main-sequence extending ~2 magnitudes below the turnoff. Despite the uncertainty that stems from, the small sample size of bright stars, comparison with the Revised Yale Isochrones suggests in our Galaxy.